Calling all creeps! - Jablonski, Carla; Stine, R. L.; Stine, R. L.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1997)
Tired of Tasha calling him names, Ricky puts an ad in the school paper that reads, "If you're a real creep, call Tasha McClain." Only something goes wrong, because now he's the one that's getting the phone calls!
"Based on the hot TV series"--Cover.
"A Parachute Press book"--T.p. verso.
Keywords: Goosebumps (Television program) -- Juvenile fiction; Horror tales; Young adult fiction